Pengembangan Media JESSTAR Sebagai Media Pembelajaran Tematik Tema 9 Kelas VI SD - Putunda Al Arif Hidayatullah; I Wayan Widana; I Ketut Suar Adnyana (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2022)
The implementation of learning in elementary schools applies thematic learning. Nevertheless, in reality, the learning process has not run optimally. It is because linkages among materials are not optimal, and there is no particular learning media for thematic learning. One of the efforts to optimize thematic learning is to develop thematic learning media. This study aims to develop JESSTAR media for thematic learning of theme 9 grade VI SD and test the learning media's feasibility. This study is developmental research in the field of education. JESSTAR media development uses the ADDIE development model (analysis, design, development, implementation, evaluation). The study was carried out at SD Negeri 1 Asahduren. The data collection method used is observation, questionnaire, and interview. The data analyzed in this research is a descriptive qualitative analysis to process data from the result of expert review and a quantitative descriptive analysis to process data on product validity and practicality test as indicators of media feasibility. The validity test results of media experts, material experts, and learning designs obtained the percentage level of validity of 95.00%, 90.67%, and 96.00%, respectively. If it is converted, then everything is in the excellent category. The results of the practicality test for teachers, small group trial, and large group trial obtained the percentage practicality level of 92.38%, 94,83%, and 93.73% respectively. If it is converted, then everything is in the excellent category. Based on the results of validity tests by experts and results of practicality tests by practitioners (teachers) and students, it can be seen that JESSTAR media is in the excellent category. Thus, it can be concluded that the JESSTAR media is suitable for use as a learning media for theme 9 in grade VI elementary schools